Factors Affecting of Myopia : A Literatur Review - Agus, Al Ihksan; Padhila, Nur Ilah; Ernasari, Ernasari; Amir, Haeril (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Myopia as refractive error will be the most common cause of visual impairment over the world until half of the world’s populations are suffer from myopia in 2020. All of age groups can get it, from adolescents and even adults. This study aimed to determine the risk factors that increase the incidence of myopia. Extensive review of the recent literature was conducted in electronic databases Pubmed, Science Direct, Wiley Online using the appropriate key words “Myopia”, “Increase Factors” dan “Effecting Factors”. The results of the search for articles after being screened through inclusion criteria and exclusion criteria were found as many as 7 research articles. Myopia can be caused by several factors such as heredity, environmental factors, and habitual factors such as work and outdoor activities, intensity of gadget use and sleep time